Aportaciones al estudio del crecimiento longitudinal del alcornoque - Molinas M.; Caritat A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The mechanisms that control the development of a particular tree architecture are for the most part poorly understood. This report describes the methodology and the preliminary results of the study of longitudinal growth in the cork tree. Measurements were taken from a 14 years-old young cork tree. Branch lengths were measured with flexible plastic rules. In addition of destructive sampling, continuous data on shoot phenology were collected. Two kinds of shoots, long and short shoots can be distinguished.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)